STATE OF THE ART EXPERIMENT: विभिन्न कालान्तर्गत तत् वाद्यों में अधुनातन प्रयोग - Upadhyay, Richa (International Journal of Research -GRANTHAALAYAH, 2015)
The tradition of many musical instruments in Indian music has been going on since time immemorial. Adi Man has not only laid the foundation of various artistic objects on the basis of his interest and intellect, but by using them, he elevated the human life from the physical plane and brought the art to the divine and supernatural world. The principles of music, Shruti, Vowel, Saptak, distance from one vowel to another, the Munchrachrachna method etc. could be proved and determined only through experiments conducted in the category of tatras. Even today, most modern experiments are being done in this way, as the change in time is visible in each object. In the same way, modern changes are also seen in the equations along with the time interval. Which we can see in the playing method as a modern experiment. Can be seen as a change in the way artists are presented. Apart from these, the composition of the instrument, the use of new instruments in place of the ancient instruments and various parts of the tantri instruments can also be seen. Out of all these topics, I have detailed in my Shodh Patra the latest usage in various parts of Tantri instruments like - tabli, tumba, ghodi (jawari), tantri, sarika, khutis, etc. which is as follows भारतीय संगीत में अनेक प्रकार के तत् वाद्यों की परम्परा आदिकाल से चली आ रही है । आदि मानव ने अपनी रुचि एवं बुद्धि के आधार पर कलात्मक विविध तत् वाद्यों की नींव ही नहीं डाली वरन् उनका उपयोग कर मानव जीवन को भौतिक धरातल से ऊँचा उठाकर कला को दिव्य तथा आलौकिक धरा पर लाकर प्रतिष्ठित कर दिया । तत् वाद्यों की श्रेणी में किये गये प्रयोगों के माध्यम से ही संगीत के सिद्धान्तों ,श्रुति, स्वर, सप्तक, एक स्वर से दूसरे स्वर की दूरी, मूछ्र्र्रच्ना पद्धति आदि को प्रमाणित व निष्चित किया जा सका । आज भी इसमें निरंतर अधुनातन प्रयोग किये जा रहे हंै, जिस प्रकार से प्र्रत्येक वस्तु में समयंातराल के साथ-साथ परिवर्तन दृष्टिगत होता है। उसी प्रकार से तत् वाद्यों में भी समयांतराल के साथ-साथ आधुनिक परिवर्तन दृष्टिगत होते हंै। जिसे हम वादन विधि में अधुनातन प्रयोग के रुप में देख सकते हैं। कलाकारों के प्रस्तुितकरण के तरीके में परिवर्तन के रुप में देख सकते हैं। इनके अतिरिक्त वाद्य की बनावट, प्राचीन वाद्यों के स्थान पर नवीन वाद्यों का प्रयोग तथा तन्त्री वाद्यों के विभिन्न अंगों में भी देख सकते हैं। इन सब विषयों में से मैने अपने षोध पत्र में तन्त्री वाद्यों के विभिन्न अंगों जैसे - तबली, तूम्बा, घोडी, (जवारी), तंत्रियाँ, सारिका, खूटियाँ, आदि में अधुनातन प्रयोग की विस्तृत व्याख्या की है जो निम्नवत है